Reassessing Sayyid Usman bin Yahya’s Critique of Sufism in Contemporary Indonesia - Siti Suniah (Al Qalam, 2025)
The transformation of Sufi practices within Indonesia’s urban setting has prompted sustained discussions concerning religious authority, orthodoxy, and engagement with modernity. In Jakarta, the rise of neo-Sufism, urban Sufism, and digitally mediated religiosity illustrates the dynamic interaction between continuity and change in Islamic spiritual traditions. This study explores Sayyid Usman bin Yahya’s nineteenth-century critique of Sufi practices and examines its relevance to the development of modern Islamic thought in Jakarta. Utilizing library research and qualitative content analysis, the study engages with Sayyid Usman’s primary texts alongside contemporary scholarly works on Sufism. The findings indicate that his opposition to religious innovations, superstitious practices, and the excessive veneration of spiritual authorities played a significant role in shaping a Sharia-oriented model of urban Sufism. This model emphasizes the primacy of the Qur’an and Hadith, promotes rational engagement in spiritual life, and demonstrates adaptability to metropolitan social conditions. By connecting classical critiques of local Sufi traditions with contemporary forms of urban religiosity, this study addresses an important gap in the literature and contributes to broader discussions on Islamic education, digital da‘wah, and Muslim identity formation in modern urban contexts.